2021
DOI: 10.1002/chem.202005459
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Properties of Lanthanide(III) Complexes with a Nonadentate Bispidine Ligand

Abstract: Eu III , Tb III , Gd III and Yb III complexes of the nonadentate bispidine derivative L 2 (bispidine = 3,7-diazabicyclo [3.3.1]nonane) were successfully synthesized and their emission properties studied. The X-ray crystallography reveals full encapsulation by the nonadentate ligand L 2 that enforces to all Ln III cations a common highly symmetrical capped square antiprismatic (CSAPR) coordination geometry (pseudo C 4v symmetry). The well-resolved identical emission spectra in solid state and in solution confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 93 publications
(170 reference statements)
1
26
0
Order By: Relevance
“…It has the advantages of an established modular assembly and a large range of available ligands with a variety of denticities and donor group combinations. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] Due to the rigidity of the tetradentate adamantane‐derived platform and additional highly preorganized pendent donor groups, bispidine ligands are known to offer efficient complexation pathways and to form very inert complexes. [25] This has been shown in a number of studies with bispidine‐based radioactive probes [25] and was also confirmed in a recent Mn II based magnetic resonance imaging study with a pentadentate bispidine.…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantages of an established modular assembly and a large range of available ligands with a variety of denticities and donor group combinations. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] Due to the rigidity of the tetradentate adamantane‐derived platform and additional highly preorganized pendent donor groups, bispidine ligands are known to offer efficient complexation pathways and to form very inert complexes. [25] This has been shown in a number of studies with bispidine‐based radioactive probes [25] and was also confirmed in a recent Mn II based magnetic resonance imaging study with a pentadentate bispidine.…”
Section: Introductionmentioning
confidence: 99%
“…The bispidine scaffold (B 1 –B 5 , L 1 , L 2 in Scheme 1) is an ideal system to test these principles. It has the advantages of an established modular assembly and a large range of available ligands with a variety of denticities and donor group combinations [21–27] . Due to the rigidity of the tetradentate adamantane‐derived platform and additional highly preorganized pendent donor groups, bispidine ligands are known to offer efficient complexation pathways and to form very inert complexes [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and Characterization of L1-PEG 2 -TATE. The synthesis of the nonadentate ligand L1 has been described previously, 32 and we have reported the possibility to attach biomolecules at the C9 position of the bispidine scaffold. 43 With the protocol generally used, the synthesis selectively produces the ligand conformation and configuration preferred for stable binding of metal ions, that is, chair−chair conformation with endo−endo configuration of the pyridine groups at C2 and C4, and the alcohol group at C9 is in antidisposition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21−27 Bispidine (3,7-diazabicyclo[3.3.1]nonane)-based ligands are adamantane derived with very rigid structures, ideal for the complexation of large metal ions such as Mn II , 28,29 Bi III , 30 Pd II , 31 and Ln III . 32 These ligands, first described by Mannich and Mohs, 33 are highly modular and allow for a large variety of denticities and donor group combinations. 34 Moreover, they combine the properties of acyclic ligands, that is, fast complexation kinetics, and macrocyclic structures, that is, enforcement of specific coordination geometries, high kinetic inertness, and thermodynamic stability.…”
Section: ■ Introductionmentioning
confidence: 99%